Demographic variables and outcomes of labour disputes. - Abdul, Fathima (My University, 2009)
The present study aimed to explore whether demographic variables are predictors of labour review case outcomes. In order to investigate the aim of the present study, two research questions were put forward. The first question centered on whether demographic variables of the parties in a case, are predictors of reviews outcomes. In addition to looking at these broader patterns, the study also focused more specifically on whether the demographic variables of presiding officers predict the outcomes of reviews of CCMA cases. The present study is classified as archival in nature and is quantitative, non-experimental and an ex post facto design. The sample for the present research was gathered by analysing Labour Review Reports that was accessed through the University of the Witwatersrand Library. A sample of 100 case reports was gathered in order to make accurate inferences from the sample about the target population. A Chi-Square test of association was conducted on the data gathered. There was no significant in relation to gender, age and case outcomes. On the other hand, race of the judge, applicant and respondent did provide evidence of significance. However, as a result of insignificance, log linear modelling could not be conducted.
Keywords: Labour disputes; Demographic variables